Bromelain treatment decreases secretion of pro-inflammatory cytokines and chemokines by colon biopsies in vitro - Onken, Jane E (Clinical immunology (Orlando, Fla.), 2008)
Oral bromelain has been anecdotally reported to decrease inflammation in ulcerative colitis (UC). Proteolytically active bromelain is known to decrease expression of mRNAs encoding pro-inflammatory cytokines by human leukocytes in vitro. To assess the effect of bromelain on mucosal secretion of cytokines in inflammatory bowel disease (IBD), endoscopic colon biopsies from patients with UC, Crohn's disease (CD), and non-IBD controls were treated in vitro with bromelain or media, then cultured. Secretion of pro-inflammatory cytokines and chemokines was measured. Significant increases in granulocyte colony-stimulating factor (G-CSF), interferon (IFN)-gamma, interleukin (IL)-1beta, IL-6, and tumor necrosis factor (TNF) were detected in the media from actively inflamed areas in UC and CD as compared with non-inflamed IBD tissue and non-IBD controls. In vitro bromelain treatment decreased secretion of G-CSF, granulocyte-macrophage colony-stimulating factor (GM-CSF), IFN-gamma, CCL4/macrophage inhibitory protein (MIP)-1beta, and TNF by inflamed tissue in IBD. Bromelain may be a novel therapy for IBD